Preparation and Characterization of Zeolite A Synthesized from Narathiwat White Clay - Sinchangreed, Abhirak; Watcharamaisakul, Sukasem; Janphuang, Pattanaphong (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
Zeolite A is a widely used synthetic zeolite known for its high ion-exchange capacity and molecular sieving properties. This study explored the synthesis of zeolite A using Narathiwat white clay as a raw material. White clay, primarily composed of kaolinite (Al2Si2O5(OH)4), is considered a cost-effective source of aluminum and silicon for zeolite synthesis. The process involves the transformation of kaolinite into metakaolin via calcination, followed by hydrothermal crystallization under controlled conditions from natural white clay without conventional high-temperature calcination. Synthesized zeolite was characterized using X-ray diffraction (XRD), Differential Thermal Analysis (DTA), scanning electron microscopy (SEM), and X-ray fluorescence (XRF) spectroscopy to determine the elemental composition of the raw white clay and the synthesized zeolite A, while Fourier-transform infrared spectroscopy (FTIR) was used to confirm its structure and purity. Furthermore, the influence of the NaOH solution and the stability temperature of zeolite A are shown in this research. The optimum conditions for achieving zeolite A were calcined at 600 °C for 3 h in the first step, followed by using autoclaves at 200 °C for 24 h with a 3 M NaOH solution. The SEM results indicated that the Narathiwat white clay could be used to synthesize zeolite A, which exhibited a cubic morphology consisting primarily of silicon and aluminum. Notably, the crystallinity was influenced by the concentration of the NaOH solution employed. Moreover, the XRD and FTIR results demonstrate the feasibility of synthesizing high-quality zeolite A. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).